2007
DOI: 10.1159/000102034
|View full text |Cite
|
Sign up to set email alerts
|

Birthmarks and Transient Skin Lesions in Newborns and Their Relationship to Maternal Factors: A Preliminary Report from Northern Italy

Abstract: Background: A total of 620 healthy term neonates, randomly selected among babies born at the San Paolo Hospital in Milan (Italy), were examined to study the relationship between birthmarks and transient cutaneous lesions in newborns of different ethnic groups. Methods: Information on sociodemographic factors and on physiopathological variables of the pregnancy was collected. Multiple logistic analyses were performed to assess associations between diagnosed skin lesions and various factors. Odds ratios (OR) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
5
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 19 publications
5
38
5
8
Order By: Relevance
“…The size of the Mongolian spot square was strongly and directly correlated with the body surface area of the infant (p=0.0001) (Figure 2 Several studies on prevalence of Mongolian spot have been conducted worldwide. The reported prevalence of the Mongolian spot variesas follows: East Africa (95.0%), Native Americans (90.0%), Korean (97.1%), China (86.3), Japan (81.5%), Nigeria (74.8%), Iran (71.3%), India (60.2-62.2%), Spain (60.0%), Taiwan (61.6%), Brazil (60.0%), Hungary (22.6%), Australia (25.5%), Italy (2-5%), Arab (8-10%), Azerbaijan (10%), and Turkey (10-12%) [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Results Of the Relevance Analysis Of Infant Mongolian Spotmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of the Mongolian spot square was strongly and directly correlated with the body surface area of the infant (p=0.0001) (Figure 2 Several studies on prevalence of Mongolian spot have been conducted worldwide. The reported prevalence of the Mongolian spot variesas follows: East Africa (95.0%), Native Americans (90.0%), Korean (97.1%), China (86.3), Japan (81.5%), Nigeria (74.8%), Iran (71.3%), India (60.2-62.2%), Spain (60.0%), Taiwan (61.6%), Brazil (60.0%), Hungary (22.6%), Australia (25.5%), Italy (2-5%), Arab (8-10%), Azerbaijan (10%), and Turkey (10-12%) [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Results Of the Relevance Analysis Of Infant Mongolian Spotmentioning
confidence: 99%
“…In general, Mongolian spot is located lower side of back and has deep blue and grey blue color [17]. According to the study of Silengo et al the classical location of Mongolian spot is the back [9].…”
Section: Results Of the Relevance Analysis Of Infant Mongolian Spotmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Mostly, these studies included the examination of 500-1000 neonates, and were conducted in Asia; [1][2][3][5][6][7][8][9] few studies on neonatal skin manifestations have been reported in Europe. [4] Some reports detected all the skin manifestations found, whereas others examined only some specifi c condition, such as erythema toxicum neonatorum (ETN).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Mostly, these studies included the examination of 500-1000 neonates, and were conducted in Asia; [1][2][3][5][6][7][8][9] few studies on neonatal skin manifestations have been reported in Europe. [4] Some reports detected all the skin manifestations found, whereas others examined only some specifi c condition, such as erythema toxicum neonatorum (ETN). [10,11] In certain studies, the correlations between skin disorders and neonatal factors (gender, gestational age, birth weight and Apgar score) were examined, while some authors [3,4,[6][7][8][9] also studied the associations with such maternal factors as age, parity, toxic habits and maternal diseases.…”
Section: Introductionmentioning
confidence: 99%